2019
DOI: 10.3390/ijerph16173207
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in PCSK9, LDLR, BCMO1, SLC12A3, and KCNJ1 Are Associated with Serum Lipid Profile in Chinese Han Population

Abstract: Unfavorable serum lipid levels are the most important risk factors for coronary artery disease (CAD), cerebral infarction, and other cardiovascular and cerebrovascular diseases. This study included 2323 Han Chinese in southern China. We collected medical reports, lifestyle details, and blood samples of individuals and used the polymerase chain reaction-ligase detection reaction method to genotype single-nucleotide polymorphisms (SNPs). Two SNPs showed a strong evidence of association with total cholesterol (TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…It is important to notice that the allele distribution of these polymorphisms varies according to the ethnic origin of the study populations. In this context, data obtained from the National Center for Biotechnology Information revealed that the individuals from Los Angeles with Mexican ancestry, Mexican mestizos, Caucasian, and Africans had a lower frequency of the c.*52 A allele (26,23,23, and 15%, respectively) than Asians (41%). Moreover, Mexican mestizos, Europeans, Africans, as well as individuals from Los Angeles with Mexican ancestry, have a lower frequency of the c.*773 G allele (23,22,16, and 26%, respectively) than the Asian population (41%) [31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to notice that the allele distribution of these polymorphisms varies according to the ethnic origin of the study populations. In this context, data obtained from the National Center for Biotechnology Information revealed that the individuals from Los Angeles with Mexican ancestry, Mexican mestizos, Caucasian, and Africans had a lower frequency of the c.*52 A allele (26,23,23, and 15%, respectively) than Asians (41%). Moreover, Mexican mestizos, Europeans, Africans, as well as individuals from Los Angeles with Mexican ancestry, have a lower frequency of the c.*773 G allele (23,22,16, and 26%, respectively) than the Asian population (41%) [31].…”
Section: Discussionmentioning
confidence: 99%
“…According to data in the literature, the impact of the LDLR gene polymorphisms on lipid plasma concentration has been proposed as the mechanism that explains the relationship between these SNPs and the higher risk of developing familial hypercholesterolemia [ 7 , 8 ]. In this context, recent studies have associated the LDLR polymorphisms (c.*52 A/G , c.*504 A/G , and c.*773 A/G ) with low levels of plasma lipids and the risk of developing familial hypercholesterolemia [ 9 , 10 , 11 , 23 ]. For example, Li et al reported that c.*773 G/G genotype is associated with decreased plasma levels of HDL-C in healthy individuals of China [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the life quality increases and dietary pattern changes, multiple factors give rise to the growing morbidity of dyslipidemia. An epidemiological study shows that dyslipidemia closely links to cardiovascular and cerebrovascular diseases, including coronary atherosclerotic heart disease and cerebral infarction [ [1]]. It is estimated that the overall morbidity of dyslipidemia in Chinese adults reaches 40.40% and continues to rise [ [2]].…”
Section: Introductionmentioning
confidence: 99%